Tests and numerical simulation of rectangular RACFST stub columns under concentric compression. (October 2020) - Yang, You-Fu; Hou, Chao; Liu, Min
Highlights: Experimental study on the performance of rectangular RACFST stub columns under concentric compression. A FEA model that can well simulate the behaviour of concentrically loaded rectangular RACFST stub columns. Simplified formulae suitable for predicting the bearing capacity of rectangular RACFST stub columns. Abstract: Tests and numerical simulation of rectangular recycled aggregate concrete filled steel tube (RACFST) stub columns under concentric compression are carried out. Eighteen specimens, including 12 RACFST specimens and 6 concrete filled steel tube (CFST) specimens as reference, with varied width-to-thickness ratio ( B / t ), depth-to-width ratio ( β ) and recycled coarse aggregate replacement ratio ( r ) are tested. The test results show that rectangular RACFST stub column specimens have similar failure pattern as their counterparts. However, the bearing capacity and the composite elastic modulus of RACFST specimens are lower than those of CFST ones while they both decrease with higher r . Moreover, the specimens with larger B / t and β possess a smaller ductility index. Numerical simulation of rectangular RACFST stub columns under concentric compression is executed using a finite element analysis (FEA) model developed based on the ABAQUS software, and the predicted results are verified by the experimental observations. The mechanism of concentrically loaded rectangular RACFST stub columns is further revealed by the FEA model. Finally, simplified formulae for the bearing capacity of rectangular RACFST stub columns are proposed, with the comparison between simplified and experimental results showing that the simplified model is a good predictor.